LncRNA NEAT1-206 regulates autophagy of human umbilical cord mesenchymal stem cells through the WNT5A/Ca2+ signaling pathway under senescence stress - Weili Wang; Yongyu Wang; Chunchun Duan; Wenjing Tian; Liyang Gao (Non-coding RNA Research)
Stem cells are crucial for maintaining bodily stability, but their regenerative abilities decline with age. This decline is marked by reduced proliferation and differentiation capacities of stem cells, as well as exhaustion of the stem cell pool. The accumulation of aged mesenchymal stem cells (MSCs) can reduce the tissue regeneration, but the molecular mechanisms influencing MSCs aging remain unclear. Moreover, collecting MSCs from elderly individuals is not suitable for observing the early response of MSCs to senescence stress, and the factors involved in early senescence remain unclear. In our previous study, we established a fast MSC aging model using D-galactose. We discovered that, while not affecting the ''stemness'' markers of mesenchymal stem cells, the expression of LncRNA NEAT1-206 was notably increased during the early stages of aging induction (within 4 days). And LncRNA NEAT1-206 was observed to be localized in the cytoplasmic matrix due to enhanced nuclear export. We found that the LncRNA NEAT1-206 could trigger autophagy through the WNT5A/Ca2+ signaling pathway, thereby decreasing senescence markers and enhancing the osteogenic differentiation of MSCs. This study elucidated the role that LncRNA NEAT1-206 as a potential key factor in conferring resistance to D-galactose-induced cell senescence at the early stage and promoting the osteogenic differentiation of MSCs. This study may provide a foundational understanding for delaying the MSCs aging process.